The design of a system for evaluating glare from small lighting sources - Joubert, Theresa (My University, 2013)
Discomfort glare is a topic that has been investigated for many years without any reasonable explanation regarding its effect on the human visual system. Results of previous research concluded that established methods have a lot of similarities in implementation; but a number of differences when comparing the results of observer's evaluations with the mathematically calculated glare ratings. Therefore, an alternative method of evaluating the influence of exposure to an unshielded light source was investigated to establish a more reliable and realistic response from observers. In order to address the discrepancies of previous evaluation systems concerning observer's varying opinions regarding the level of discomfort experienced, it was decided to investigate the feasibility of evaluating the brain activity of the observers exposed to an unshielded incandescent lamp. This was done in order to facilitate the differences in each individual observer's sensitivity to bright light sources and the influence of personal taste therefore, eliminating the effect of personal interpretation. The main purpose of this study was to determine whether it would be possible to get any response regarding brain functions when an observer is exposed to a bare light source. In order to determine the pathway of visual stimuli it was necessary to investigate the operating principles of the human eye in detail. Because the eye is only an instrument that makes seeing possible; it was also important to investigate the brain and all its different functions. The part of the brain where visual interpretation takes place was indicated as the occipital lobe. This is the part of the brain monitored for any change of functional status by taking measurements with an electroencephalogram (EEG). Measurements were indeed possible; it was presented as a suppression of the alpha brain activity. During the testing procedure it was observed that the observers were not equally photosensitive. There was also a difference in the amount of alpha suppression with the observer's eyes open and closed respectively. Because the alpha rhythm has a tendency to increase with closed eyes it was much easier to notice the suppression.
Thesis (Magister Technologiae - Discipline Electrical Engineering, Faculty of Engineering) -- Vaal University of Technology
Keywords: Lighting; Discomfort glare; Incandescent lamps; Light sensitivity; Photosensitivity; 621.321; Electric lighting